2018
DOI: 10.1051/e3sconf/20184704001
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Toxicity Tests of Mercury (Hg) to Nilem Fish (Osteochilus hasselti) Gills Tissue Damage

Abstract: Industry development in Indonesia resulted in sewage and polluting heavy metals such as mercury (Hg). These pollutants will be harm organisms that live at aquatic environment. Fish gills could be damage due to exposure by mercury. To know the influence of mercury’s toxic against aquatic organisms by using toxicity test. An aquatic organism, which is usually used as toxicity test, is nilem fish (Osteochilus hasselti). The objective of the study was to determine the value of LC50-96 hours in a toxicity test of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Fish would efficiently absorb methyl mercury, but would at the same time slowly release it. In this study, sublethal concentration was used, in reference to the concentration below the LC50-96 hour of Hg toxicity in silver sharkminnow at 0.396 ppm (Siregar et al, 2018). Sublethal influence occurs in the fish organs, causing damages to the liver, decreasing the amount of blood, reducing the potential for breeding, growth and so on.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish would efficiently absorb methyl mercury, but would at the same time slowly release it. In this study, sublethal concentration was used, in reference to the concentration below the LC50-96 hour of Hg toxicity in silver sharkminnow at 0.396 ppm (Siregar et al, 2018). Sublethal influence occurs in the fish organs, causing damages to the liver, decreasing the amount of blood, reducing the potential for breeding, growth and so on.…”
Section: Resultsmentioning
confidence: 99%
“…The design used in this study was a Completely Randomized Design (CRD), with 4 treatments and 3 replications, namely: Treatment A = 0.08 ppm; B = 0.16 ppm; C = 0.24 ppm; and control = without addition of Hg. The determination of this sublethal concentrations was based on previous research carried out by Siregar et al (2018) who found LC50-96 hours in bonylip barb fish (Osteochilus hasselti) through toxicity test of Hg at 0.3938 ppm. Fish were dissected, muscle was removed and washed in distilled water, then dried at 80°C for 72 hours.…”
Section: Hg Accumulation Proceduresmentioning
confidence: 99%
“…Heavy metals are dangerous pollutants that are persistent and toxic, that cannot be metabolized and cannot be excreted through biological processes, because heavy metals can accumulate in various components of the ecosystem (water, sediment, flora, and fauna) [PRAYOGO et al 2016;SIREGAR, PRAYOGO 2017;SIREGAR et al 2018].…”
Section: Introductionmentioning
confidence: 99%